From Evidence to Action: Applied Economic Studies and the Crop Observatory for Breeding Rice Research - Rivera Vasco, Tatiana Carolina; Buritica Casanova, Alexander; D'croz Pardo, Silvia Alejandra; Fajardo Reyes, Nicolas; Cardona Montoya, Clara Isela; Ramos Orozco, Catalina; Vergara Lozano, Jose Daniel; Pedreros Pérez, Ricardo Andrés; Nasner Tacan, Hans; Caleno Ruiz, Edwin Ernesto; Esponda Bernal, Maria Del Mar; Ossa Arias, Luis Miguel; et al. (2025)
This presentation highlights how applied economic research supports the rice breeding program by linking evidence with decision-making. Through studies on farmers’ trait preferences, consumer willingness to pay for biofortified rice, and impacts of climate forecasts, technical assistance, and input subsidies, the research identifies what drives technology adoption and productivity gains. Economic evaluations show that over 1,100 rice varieties have been released in Latin America and the Caribbean, with CIAT-related lines delivering strong returns on investment. The work emphasizes that yield and grain quality remain key farmer priorities, while gender and household decision-making shape adoption outcomes. Complemented by the Rice Crop Observatory, which integrates data on production, climate, and markets, these efforts create a unified evidence base to guide breeding priorities, policy design, and foresight analysis, helping align innovations with farmers’ needs and strengthen the overall impact of rice research across the region.